POTENSI BIJI Hoya UNTUK PERKEMBANGBIAKAN DAN KONSERVASI: STUDI KASUS PADA Hoya parasitica Wall. - Rahayu, Sri; Sutrisno, Sutrisno (Buletin Kebun Raya, 2007)
Seed characteristics and seed germination behaviour of Hoya parasitica Wall. (Asclepiadaceae) were observed to study the potentials of the seed for propagation and genetic conservation of the species. Seeds were collected from follicles produced by Hoya collection of Bogor Botanical Gardens. They are small, thin, plumed and showing a comose type. The weight of 100 seeds was 0.7 â 0.9 gram and the water content was 26 â 30% at the time of fruit opening. The water content decreased rapidly to 12.7% and 21.4% after one day of storage in a desiccator containing silica gel and in the open air, respectively. This is in accordance with the natural behaviour of the seed that is dispersed mainly by wind. In general, the seeds were easy to germinate (up to 99% total germination), both in the dark and under natural light, and there was no substantial dormancy encountered during seed germination. The seeds were able to germinate up to 60% while the water content was 3.8%, suggesting the possibilities of long-term storage of the seed for plant genetic resources conservation.